2013
DOI: 10.1016/j.compositesb.2013.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of using different types of SiO2 nanoparticles on the mechanical properties of binary blended concrete

Abstract: The aim of this study was to assess the effects of two different types of SiO2 nanoparticles (N and M series) with different ratios on the workability and compressive strength of developed binary blended concretes cured in water and lime solution as two different curing media. N and M series SiO2 nanoparticles with an average size of 15 nm were used as obtained from the suppliers. Fresh and hardened concretes incorporating 0.5%, 1.0%, 1.5% and 2.0% of N and 2% of M series nanoparticles with constant water to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(61 citation statements)
references
References 31 publications
7
52
0
Order By: Relevance
“…It can be seen that viscosity follows a non-linear trend with respect to nS content and that maximum viscosity values correspond to an intermediate nS content of about 2%, regardless of SP dosage. This result is consistent with the findings of other authors, who reported significant loss of workability in concretes with nS contents of up to 2%[37].The effect of variations in SP dosage on viscosity is more noticeable with higher FA contents, as shown inFigure 3, where an FA content of 12.5% is assumed. In this case, the maximum viscosity values corresponded to the same intermediate nS content of about 2%, but in addition it was observed that increasing SP dosage significantly increased viscosity.…”
supporting
confidence: 94%
“…It can be seen that viscosity follows a non-linear trend with respect to nS content and that maximum viscosity values correspond to an intermediate nS content of about 2%, regardless of SP dosage. This result is consistent with the findings of other authors, who reported significant loss of workability in concretes with nS contents of up to 2%[37].The effect of variations in SP dosage on viscosity is more noticeable with higher FA contents, as shown inFigure 3, where an FA content of 12.5% is assumed. In this case, the maximum viscosity values corresponded to the same intermediate nS content of about 2%, but in addition it was observed that increasing SP dosage significantly increased viscosity.…”
supporting
confidence: 94%
“…The improving percentage of compressive strength reaches about 18% with respect to the control mixes. The increase can be due to the fact that calcium hydroxide compounds existing in lime solution react with nanoparticles in their surface areas to form additional C-S-H gel thereby increasing compressive strength [12].…”
Section: Specimen Preparationmentioning
confidence: 99%
“…Using nano-particles can lead to novel properties in concrete. It causes an improvement in the mechanical properties and durability of concrete [6][7][8]. A lot of research has been carried out over the last years in order to understand the influence of nanoparticles on cement and concrete properties [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%